Knowing Iblis: Study of Thematic Interpretation of Devil's Pride - Achmad Achmad (International Journal of Islamic Thought and Humanities, 2022)
The controversy about Iblis as a "convicted" creature, cursed and expelled from various heavenly pleasures is a dramatic and perennial narrative in every divine religion. Since God proclaimed that he would create the first ruling creature on Earth [read Adam], Iblis not only presented himself as a dissident and seducer of Adam and his descendants, as the conclusion of the classical and modern interpretations above but also at the same time a symbol of negative predisposition or personification of crime, borrowing Rahman's term. This means that every form of crime committed by humans, whether in the form of murder, rape, waste, corruption, war, moral misconduct, etc., as often happens in various aspects of contemporary human life is the personification of modern Ibises.